2014
DOI: 10.3389/fimmu.2014.00514
|View full text |Cite
|
Sign up to set email alerts
|

From Monocytes to M1/M2 Macrophages: Phenotypical vs. Functional Differentiation

Abstract: Studies on monocyte and macrophage biology and differentiation have revealed the pleiotropic activities of these cells. Macrophages are tissue sentinels that maintain tissue integrity by eliminating/repairing damaged cells and matrices. In this M2-like mode, they can also promote tumor growth. Conversely, M1-like macrophages are key effector cells for the elimination of pathogens, virally infected, and cancer cells. Macrophage differentiation from monocytes occurs in the tissue in concomitance with the acquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
1,489
2
28

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,638 publications
(1,560 citation statements)
references
References 229 publications
(343 reference statements)
41
1,489
2
28
Order By: Relevance
“…Little gene expression of IL‐1β was observed in M‐MΦ. The polarized macrophages phenotypes exhibited by rabbit macrophages were similar to that of human and mouse macrophages based on cytokine profiles and other parameters measured 22. In this study, we maintained having M‐CSF during the stimulation step (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Little gene expression of IL‐1β was observed in M‐MΦ. The polarized macrophages phenotypes exhibited by rabbit macrophages were similar to that of human and mouse macrophages based on cytokine profiles and other parameters measured 22. In this study, we maintained having M‐CSF during the stimulation step (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…41 RON activation has previously been reported to skew macrophages to the M2 phenotype and attenuate inflammation. 42 When we compared expression levels of differentially regulated genes in our study with previously published datasets corresponding to defined M1 versus M2 states, 43 we found that RON activation did not strictly correlate with either the M1 or M2 state ( Fig S2 ).…”
Section: Resultsmentioning
confidence: 97%
“…TAMs and circulating immature myeloid cells, so-called myeloid-derived suppressor cells (MDSCs), play crucial roles in maintaining the tumor microenvironment together with Tregs (16)(17)(18)(19)(20). In the differentiation cascade of myeloid cells in the tumor-bearing host (21), TAMs are derived from Ly6C + monocytes (monocytic MDSCs) in the blood (21).…”
Section: Discussionmentioning
confidence: 99%